2021
DOI: 10.1111/jocd.14125
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to compare the effectiveness and safety of adsorbent lotion containing tapioca starch, spent grain wax, Butyrospermum parkii extract, argania spinosa kernel oil, aloe barbadensis, rosehip oil, and allantoin with a low‐potency topical corticosteroid in the treatment of intertrigo

Abstract: Background Intertrigo is an inflammatory skin‐fold condition. Candida infections may occur concurrently or afterward. Topical corticosteroids may reduce inflammation but exacerbate Candida infections. The treatment is contentious. Objective To evaluate the efficacies and safety of adsorbent lotion containing tapioca starch, spent grain wax, Butyrospermum parkii extract, argania spinosa kernel oil, aloe barbadensis, rosehip oil, and allantoin for the treatment of mild‐to‐moderate intertrigo, relative to 1% hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Beyond wound healing, RO has been suggested to have other skin benefits. Leeyaphan et al 20 reported a significant reduction in pruritus in intertrigo patients treated with a lotion containing RO, showing a similar level of patient satisfaction compared to corticosteroid treatment. While these findings indicate the potential versatility of RO in dermatological applications, more research is needed to validate these results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Beyond wound healing, RO has been suggested to have other skin benefits. Leeyaphan et al 20 reported a significant reduction in pruritus in intertrigo patients treated with a lotion containing RO, showing a similar level of patient satisfaction compared to corticosteroid treatment. While these findings indicate the potential versatility of RO in dermatological applications, more research is needed to validate these results.…”
Section: Discussionmentioning
confidence: 92%
“…In this context, the findings from the studies included in this review may be due to RO's antagonistic effect on TGFβ1, 6 promoting healthier tissue healing and decreasing scar size. Moreover, RO demonstrated anti‐inflammatory and anti‐scarring effects, as indicated by its inhibitory effects on inflammatory mediators such as IL‐1R and IL‐1 6,20,21 . Overall, Lei et al's animal trial demonstrated a notable decrease in scar size in the mice treated with RO compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, leaf extracts from Camellia sinensis and Argania spinosa protect the epidermis from PM2.5 exposure-induced oxidative stress and subsequent chemokine release. These extracts are considered to be safe in the present practices of use and concentration, although continuous safety evaluation is needed (Becker et al, 2019;Leeyaphan et al, 2022). Therefore, Camellia sinensis and Argania spinosa extracts could be added to a novel cosmetic that protects skin from air pollution.…”
Section: Resultsmentioning
confidence: 99%
“…(Khallouki et al, 2017). In a randomized controlled trial, an absorbent lotion that has plant ingredients with argan tree oil showed similar anti-inflammatory efficacy on skin-fold conditions to 1% hydrocortisone cream (Leeyaphan et al, 2022).…”
Section: Argan Tree (Argania Spinose L Family Sapotaceae)mentioning
confidence: 99%
“…It has been shown that topical application of argan oil improved barrier function and increased water‐holding capacity (Khallouki et al, 2017). In a randomized controlled trial, an absorbent lotion that has plant ingredients with argan tree oil showed similar anti‐inflammatory efficacy on skin‐fold conditions to 1% hydrocortisone cream (Leeyaphan et al, 2022).…”
Section: Skincarementioning
confidence: 99%